Erratum to: New biotextiles for tissue engineering : development, characterization and in vitro cellular viability - Almeida, L. R. (2013)
This work proposes biodegradable textile-based structures for tissue engineering applications. We describe the use of two polymers, polybutylene succinate (PBS) proposed as a viable multifilamentand silk fibroin (SF), to produce fibre-based finely tuned porous architectures by weft knitting. PBS is here proposed as a viable extruded multifilament fibre to be processed by a textile-based technology. A comparative study was undertaken using a SF fibre with a similar linear density. The knitted constructs obtained are described in terms of their morphology, mechanical properties, swelling capability, degradation behaviour and cytotoxicity. The weft knitting technology used offers superior control over the scaffold design (e.g. size, shape, porosity and fibre alignment), manufacturing and reproducibility. The presented fibres allow the processing of a very reproducible intra-architectural scaffold geometry which is fully interconnected, thus providing a high surface area for cell attachment and tissue in-growth. The two types of polymer fibre allow the generation of constructs with distinct characteristics in terms of the surface physico-chemistry, mechanical performance and degradation capability, which has an impact on the resulting cell behaviour at the surface of the respective biotextiles. Preliminary cytotoxicity screening showed that both materials can support cell adhesion and proliferation. These results constitute a first validation of the two biotextiles as viable matrices for tissue engineering prior to the development of more complex systems. Given the processing efficacy and versatility of the knitting technology and the interesting structural and surface properties of the proposed polymer fibres it is foreseen that the developed systems could be attractive for the functional engineering of tissues such as skin, ligament, bone or cartilage.